Evaluation of lipid peroxidation [TBARS] and antioxidant status for monitoring oxidative stress in students of Physical education and sport science - Mahdi, Elham Abed; Hamad, Haider Fayyadh (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The main purpose of this study was to demonstrate the impact of different exercises on the oxidative stress in students of first class physical education and sport sciences in Kufa university/ Iraq. Plasma enzymetic [super oxidedismutase (SOD),catalase ( CAT), glutathione reductase (GSH) and glutathione peroxidase (GPX) activities ], non enzymetic [ total antioxidant capacity (TAC), uric acid (UA) and some serum trace elements(Cu, Zn, Se)] as antioxidant ,and a marker of lipid peroxidation thiobarbituric acid –reactive substances[TBARS] were measured in( 30) students in beginning year before they received any training or exercise programs (T0) and after three months (T1) then after 6 months (T2), when these students exposure for multi and variety training and games who take as lessons in first class of physical education and sport sciences faculty which is moderate physical activities and mixed aerobic and anaerobic exercise. Our results showed increased plasma values of (SOD) ,(Cu, Zn, Se) after 3 months (T1) and 6 months (T2) when compared at baseline (T0), while plasmatic (CAT), (GPX),(GSH) were similar in three groups. On the other hand a lower (TAC) levels after 3 months (T1)and 6 months (T2) when compared with levels at base line(T0). Nevertheless, (TBARS) levels were found to be significantly higher in the students after 6 months when compared with levels at 3 months and at base line levels